Social Factors in The Prevention of Early Marriage and Premature Childbirth in Uzbek Families (On the Example of The Fergana Valley) - BALTABAEVA, MANZURAKHON MIRZAJANOVNA (The journal of contemporary issues in business and government, 2021)
The article is based on a study of the social situation, the results of the practical work of civil society organizations on the social protection of adolescent girls who marry early in Uzbek families and affected by the negative consequences of early childbirth were analyzed. There is also new methods for solving these problems by conducting sociological surveys among mothers of adolescent, elder and olders on the problem of changing attitudes towards early life and early childbirth in Uzbek families, and development of a methodological guide based on the analytical results, organizing roundtables on "How to radically change the worldview of mothers and mothers-in-law in the preparation of girls for safe childbirth in Uzbek families?"